Pengaruh Penambahan Azolla pinnata pada Ransum terhadap Pertambahan Bobot Itik Mojosari Jantan dan Analisis Usaha - Ridho Aka Qomarizzaman; Mohamad Amin; Abdul Gofur; Agus Dharmawan (Universitas Negeri Malang, 2017)
Meat is food source of animal protein could be consumed to fill up food needs. Duck is poultry commodity that has the potential to fill up meat needs. Duck farming needs more capital cost in buying feedstuff. Farmer should provide alternative feed to minimize cost of production. Alternative feed ingredients could be given for example Azolla pinnata. Azolla pinnata is a weed grows in aquatic areas for example lakes, swamps and ponds cultivated. The aim of this research are 1) to find out difference treatments of Azolla pinnata addition to the weight of male Mojosari ducks, and 2) the effective addition of Azolla pinnata. This research is experimental research using 5 treatments (without addition of Azolla pinnata, addition of Azolla pinnata 5%, 10%, 15% and 20%) with replication 5 times each repetition. Data collection was done by calculating body weight gain, Feed Consumption Rate (FCR) and analysis of business. The result of this research is the addition of Azolla pinnata on ration influencing the increase of duck weight of male Mojosari and the addition of Azolla pinnata 20% most effective and can be applied for male Mojosari duck.